2003
DOI: 10.1093/jnci/djg060
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Tamoxifen Use, and Outcomes in Women With Estrogen Receptor-Positive Early-Stage Breast Cancer

Abstract: For women with lymph node-negative, ER-positive breast cancer, obesity was not associated with a material increase in recurrence risk or a change in tamoxifen efficacy. However, because obesity was associated with increased risks of contralateral breast cancer, of other primary cancers, and of overall mortality, it may influence long-term outcomes for breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
4
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(205 citation statements)
references
References 77 publications
13
179
4
9
Order By: Relevance
“…Higher BMI has been related to more advanced stages of breast cancer at diagnosis in terms of tumour size [38]. Obesity appears not to interfere with the efficacy of tamoxifen in women with lymph-node negative, oestrogen receptor-positive breast cancer [39].…”
Section: Biological Mechanismmentioning
confidence: 99%
“…Higher BMI has been related to more advanced stages of breast cancer at diagnosis in terms of tumour size [38]. Obesity appears not to interfere with the efficacy of tamoxifen in women with lymph-node negative, oestrogen receptor-positive breast cancer [39].…”
Section: Biological Mechanismmentioning
confidence: 99%
“…Several studies (Dignam et al, 2003;Berclaz et al, 2004;Loi et al, 2005) reported a higher risk of death in patients with BMI above 30 compared to those with a BMI less than 25. Furthermore, results from the Nurses' Health Study (Kroenke et al, 2005) showed that the association of weight gain after breast cancer diagnosis and increased breast cancer mortality was limited among women who had normal weight (BMI<25) before diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews report that roughly two-thirds of the studies conducted in the last decade have shown that higher body mass index (BMI) or body weight (overweight or obesity) are significant risk factors for recurrent disease or decreased survival [1;3;4], with only 25% showing a null effect and 10% suggesting a significant inverse association [3]. However, two recent randomized clinical trials, which offer the advantages of large populations in which clinical prognostic factors are well defined, have found an effect of obesity only on overall survival [5] or only on new contralateral breast disease, but not recurrence [6]. Several plausible mechanisms have been proposed to support the effect of body weight on breast cancer growth.…”
Section: Introductionmentioning
confidence: 99%